2018
DOI: 10.1038/s41467-018-03759-y
|View full text |Cite|
|
Sign up to set email alerts
|

Precisely printable and biocompatible silk fibroin bioink for digital light processing 3D printing

Abstract: Although three-dimensional (3D) bioprinting technology has gained much attention in the field of tissue engineering, there are still several significant engineering challenges to overcome, including lack of bioink with biocompatibility and printability. Here, we show a bioink created from silk fibroin (SF) for digital light processing (DLP) 3D bioprinting in tissue engineering applications. The SF-based bioink (Sil-MA) was produced by a methacrylation process using glycidyl methacrylate (GMA) during the fabric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
531
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 671 publications
(582 citation statements)
references
References 60 publications
(67 reference statements)
22
531
1
Order By: Relevance
“…However, the rigidity of native silk is smaller compared to that in [4], so introduction of methacrylic moieties makes the material similar to the osseous tissue. Our study showed that the MG63 cells can attach, proliferate, and survive on FbMA-F-et films, indicating a good cytocompatibility of the scaffold ( Figure 6A-C) [18,39]. Cell-substrate interactions are crucial for a plethora of physiological processes, including cell growth and differentiation, tissue remodeling, regeneration, viability, immune responses, etc.…”
Section: Biological Propertiesmentioning
confidence: 83%
“…However, the rigidity of native silk is smaller compared to that in [4], so introduction of methacrylic moieties makes the material similar to the osseous tissue. Our study showed that the MG63 cells can attach, proliferate, and survive on FbMA-F-et films, indicating a good cytocompatibility of the scaffold ( Figure 6A-C) [18,39]. Cell-substrate interactions are crucial for a plethora of physiological processes, including cell growth and differentiation, tissue remodeling, regeneration, viability, immune responses, etc.…”
Section: Biological Propertiesmentioning
confidence: 83%
“…25B) absorbs at 375 nm and is less toxic than Irgacure. 106,159,170 Eosin Y (2′,4′,5′,7′tetrabromofluorescein disodium salt, Fig. 25C) absorbs at 514nm (blue visible light), which induces less oxidative stress for cells.…”
Section: Uv Photo-initiatorsmentioning
confidence: 99%
“…21C). 159 Functionalization has been performed on the backbone of proteins such as gelatin and silk fibroin, 159 oligosaccharides including hyaluronic acid, 157 and on the extremities of linear or branched PEG. A wide range of methacrylated, dimethacrylated, and diacrylated ( Fig.…”
Section: Introduction Of Acrylate Derivativesmentioning
confidence: 99%
“…For example, it could be used to generate dental models with high accuracy [3], and cartilage with proper and satisfactory biomechanical properties [4]. In addition, the DLP technique could also produce samples with predetermined internal structures for highly complex organs, including the trachea, heart, lung, and vasculatures [5]. Recently, the DLP technique has been used to prepare solid preparations for oral drug administrations.…”
Section: Introductionmentioning
confidence: 99%